A artesania sociológica de Heleieth Iara B. Saffioti (1934–2010): trajetória e práxis - Moraes, Samantha Camacam de (2025)
How are ideas born? How does lived experience shape the concepts that, in turn, become tools for transforming life itself, both singular and collective? Seeking to answer these questions, this dissertation examines the trajectory of the Brazilian sociologist Heleieth Iara Bongiovani Saffioti (1934-2010) unraveling the web of interdependencies that made her improbable journey possible. Originating from a rural background and endowed with limited capital, she dedicated her life to examining the “hidden Brazil” – that of women – a project initiated with her seminal postdoctoral thesis, A mulher na sociedade de classes: mito e realidade (1969). From this point onward, a career firmly grounded in praxis unfolded, which this study reconstructs in light of her positions, dialogues, productions, and reception within the national and international intellectual field, particularly in France. Based on an extensive body of sources (including institutional and personal archives, interviews, Saffioti's academic production, and periodical archives) and in biographical approaches, with an emphasis on the work of Daniel Bertaux, Françoise Battagliola et al., Howard Becker, and Pierre Bourdieu, this study situates Saffioti's familial, professional, and militant dimensions, analyzing them in their dynamic and contradictory relationship with the political-intellectual circles and the socio-historical scene of her time. Heleieth Saffioti's trajectory, from a primary school teacher to the prestigious écoles françaises, serves as a mirror through which to observe the contradictions of a Brazil in transition, oscillating between the promise of modernization and the persistence of archaic structures. Situated within the tension between agency and determinism, she broke with certain social destinies – though not with tradition, remaining a teacher – by contributing decisively to the consolidation of women’s studies in Brazil. Propelled by feminist mobilizations from the 1970s onward, she leveraged her intellectual authority in political struggles, crafting a form of sociological artisanship attentive to the margins precisely because it stemmed from one. By refusing her canonization as the “pioneer” of Brazilian feminism, this thesis offers an interpretation of her life and work by presenting Heleieth Saffioti's "other knot": the one that binds subjectivity to socio-historical conditions.